Individual and simultaneous determinations of phenothiazine drugs using PCR, PLS and (OSC)–PLS multivariate calibration methods - REZA BEHJATMANESH-ARDAKANI; MOHAMMAD REZA HORMOZI NEZHAD; MOHAMMAD MAZLOUM ARDAKANI; MOHAMMAD ALI KARIMI; HAMZEH AMIRYAN (Journal of the Serbian Chemical Society, 2008)
Individual and simultaneous determinations of some phenothiazine drugs are described. The individual determination method is based on the reaction of chlorpromazine hydrochloride (CPH), promethazine hydrochloride (PH), trifluoperazine hydrochloride (TFPH), trimipramine maleate (TPM) and thioridazine hydrochloride (TRDH) with complex of [Fe(Bpy)3]3+. In the presence of phenothiazine derivatives, [Fe(Bpy)3]3+ is reduced easily to the coloured complex [Fe(Bpy)3]2+, which shows an absorption maximum at 525 nm. The individual method is highly sensitive and suitable for 0.3–190 mg ml-1 concentrations, with detection limits in the range 0.18–2.46 mg ml-1. Simultaneous kinetic–spectrophotometric determination of ternary mixture of CPH, PH and TPM using principal component regression (PCR), partial least squares (PLS) and orthogonal signal correction (OSC)–PLS multivariate calibration methods is also described. The simultaneous methods are based on the difference observed in the reduction rate of the [Fe(Bpy)3]3+ complex with CPH, PH and TPM in acidic media. The results showed that the simultaneous determination of CPH, PH and TPM can be performed in the concentration ranges of 0.5–120.0, 0.3–80.0 and 5.0–100.0 µg ml-1, respectively, for three methods (PCR, PLS and OSC–PLS). The root mean square errors of prediction (RMSEP) of CPH, PH and TPM were 0.346, 0.663 and 0.820 (for PCR) 0.317, 0.659 and 0.830 (for PLS) and 0.087, 0.124 and 0.085 (for OSC–PLS), respectively. The proposed methods were successfully applied to the individual and simultaneous determination of phenothiazine derivatives in pharmaceutical preparations, the results of which compared well with those obtained by the official method, and several synthetic (spiked) samples, whereby satisfactory results were obtained.